Half-full or half-empty: COVID-19 anxiety moderating the effects of social entrepreneurial intent and future-time perspective on nascent entrepreneurs deciding a clothing venture - Calupas, Esmeraldo L., Jr. (Animo Repository, 2022)
Time, whether viewed as an illusion or a nonspatial continuum, is evidently important to members of society, even in this time of the COVID-19 pandemic. Yet, Time is scarcely ever studied as an antecedent to societal phenomena. For such a reason, this paper studied an aspect of Time, namely Future-Time Perspective (FTP) or the expansive perception of time in the future. FTP was measured to determine if it can influence the intent of eventually creating a social venture, at a time of COVID-19 anxiety. Results from the simple linear and moderated regression showed that a relationship exists between FTP and SEI. It was determined that it is possible for an individual, who has an expansive perception of time in the future, to eventually start a social entrepreneurship. This possibility is attributable to his or her perceived future’s available time and exploitable opportunities to select and pursue social entrepreneurship as a goal. However, such an interaction effect was determined insusceptible to the moderation of COVID-19 anxiety; that an individual’s expansive perception of his or her time in the future would not be narrowed by anxiety or fear of the virus. With such moderation being unsupported, experimentation using multiple linear regression determined that COVID-19 anxiety can decrease individuals social entrepreneurial intent; that anxiety towards the virus diminishes the emotional intelligence of individuals to respond more effectively to their own feelings, preventing them from engaging in socially appropriate ways to assist others, such as through engaging in social entrepreneurship. In essence, this study showed that having an expansive perception of time in the future can increase the intent of individuals to start a social entrepreneurship. Being anxious of COVID-19 however, could lower such intent, as it detriments emotional intelligence which is important to financial and social value creation.